Giant dorsal lipofibromatosis in an infant: a case report - Zhiyu Li; Yuqing Zou; Guangqi Xu; Jianhai Bi; Ran Huo (BMC, 2022)
Abstract Background Lipofibromatosis is a rare, benign, soft tissue tumor that usually presents in children. Low incidence and lack of specificity in clinical presentation make its diagnosis difficult. Case presentation This is a case report of a patient with a giant lipofibromatosis on the back that resembles an infantile hemangioma, which posed great difficulty in diagnosis due to atypical clinical manifestations. After the postoperative pathological and immunohistochemical examination and fluorescence in situ hybridization, the patient was finally diagnosed with lipofibromatosis. Conclusions The incidence of fibromatosis was low. This case presents an atypical clinical manifestation since the tumor growth was on the back, and this can easily cause misdiagnosis. This case suggests that the diagnosis of lipofibromatosis depends on the pathology and fluorescence in situ hybridization.